Teleworking: An integrative review of international literature - Leite, Ana Luiza; Lemos, Dannyela da Cunha; Schneider, Wilnei Aldir (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The purpose was to analyze the scientific production available in international databases on telework in order to verify the volume of production and to identify the articles' focus of study through the integrative review. Scientific production is growing, with a large number of review articles (12). Regarding empirical articles, with a predominantly quantitative approach, there is a low rate of publication in public organizations. The studies focus on the search for impacts caused by implementing telework for both the worker and the organization. There are few studies of longitudinal nature and few combining the various actors involved in telework, especially with respect to work teams.